Half a century in sports biomechanics: bridging the gap between researchers and practitioners - Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The lecture will analyse the development of the relationship between sports biomechanics and coaching over a period of 50 years. The key tenants of the Society's aims and ambitions will be central to the lecture. Foundations of the field of study as introduced by Geoffrey Dyson will be reviewed. Changes in methods of data collection and analysis will be considered alongside developments in computing from mainframe to smartphone. Examples will be drawn from studies throughout the period to illustrate the progress which has been made, with the challenges still to be met being highlighted along the way. The lecture will be a personal analysis of the subject's development through a summary of ideas and experiences which have influenced my thinking on the complex relationship between enhancing understanding of movement and transferring these ideas into practice.